2020
DOI: 10.1371/journal.pone.0243549
|View full text |Cite
|
Sign up to set email alerts
|

Closing the gender gap at academic conferences: A tool for monitoring and assessing academic events

Abstract: The importance of participation in academic conferences is well known for members of the scientific community. It is not only for the feedback and the improvement of the work, it is also about career development, building networks and increasing visibility. Nevertheless, women continue to be under-represented in these academic events and even more so in the most visible positions such as speaking roles. This paper presents the development of a tool based on performance indicators, which will allow monitoring a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 57 publications
(107 reference statements)
1
28
0
Order By: Relevance
“…As we emerge from COVID-19 restrictions, temporary fixes like virtual conferences may offer long-term solutions for some of the current underrepresentation of women at professional meetings in addition to ongoing efforts to create gender balance in scientific representation ( Corona-Sobrino et al, 2020 ). Organizers must continue to prioritize and promote female, early career, and diverse faculty by inviting them for virtual (and in-person) presentations to bolster their visibility and curriculum vitae, both of which are important for promotion and tenure.…”
Section: Opportunities and Recommendationsmentioning
confidence: 99%
“…As we emerge from COVID-19 restrictions, temporary fixes like virtual conferences may offer long-term solutions for some of the current underrepresentation of women at professional meetings in addition to ongoing efforts to create gender balance in scientific representation ( Corona-Sobrino et al, 2020 ). Organizers must continue to prioritize and promote female, early career, and diverse faculty by inviting them for virtual (and in-person) presentations to bolster their visibility and curriculum vitae, both of which are important for promotion and tenure.…”
Section: Opportunities and Recommendationsmentioning
confidence: 99%
“…As mentioned before, gender-based stereotype threat is even more pervasive in academic environments in which men typically predominate in prestigious positions. Men's prevalence in societies' boards and as speakers at societies' meetings, absence of childcare facilities, and additional costs when caregivers are needed create an even more hostile environment for women's engagement in higher status roles ( 22 , 26 , 32 ). This is an important issue inasmuch as recent studies have shown that the COVID-19 pandemic will increase the gender gap in science, especially for mothers of young children ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a paper by Corona-Sobrino et al ( 26 ) proposed a more comprehensive model to assess gender gap in academic events, broadening the approaches to compile data on organizational structure and women's participation and attitudes. Here, due to limited data availability, we focus on gender balance among speakers at the society's meetings and the composition of the directory boards.…”
Section: Introductionmentioning
confidence: 99%
“…Conferences frequently lack diverse presenters [12][13][14][15]. We recommend that organizers examine their list of invited speakers with the express purpose of ensuring adequate representation and to determine if it is representative of the general population.…”
Section: Diversifying Speaker Listsmentioning
confidence: 99%
“…many efforts, several conferences struggle to foster diversity and inclusivity in both attendance and invited speakers [12][13][14][15]. This is particularly harmful to underrepresented scientists as failure to include underrepresented groups in invited speaker lists, or amongst plenary speakers, can further compound the lack of diversity by alienating the remaining diverse trainees [12,16].…”
mentioning
confidence: 99%